TINJAUAN YURIDIS TERHADAP PELECEHAN VERBAL DAN PENGANIAYAAN RINGAN - Muhamad Fathur Rohmi; Itok Dwi Kurniawan (Universitas Slamet Riyadi, 2024)
Abstract The unitary state of the Republic of Indonesia is one of the major countries that prioritizes applicable legal provisions. One of the fields of law in order to maintain order and security of Indonesian citizens themselves is criminal law. Differences can sometimes affect the interaction process and can trigger conflicts either motivated by different interests, and then cause reactions either subtly in the form of conflicts of ideas or violently in the form of violence. Problem in case file B/405/VIII/2023/Sek. Ja with a brief description when the witness named Fajar Alwiyuda was asked for information that it was true that the witness had been molested by the suspect Rifki Agoesti on Saturday, May 20, 2023 at approximately 22.00 WIB at Kp. Cakung Rt 01/05 Kel. Jatisari Kec. Jatiasih Bekasi City. The legal basis and elements of the legal provisions of the case proved that the defendant was charged with Article 352 of the Criminal Code investigated by the investigator. The conclusion obtained is correct There has been a criminal offence of